Voltage Stabilization of a Wind Turbine with STATCOM Using Intelligent Control Techniques - S. A. Gawish; S. M. Sharaf; M. S. El-Harony (IAES Indonesian Section, 2016)
Application of FACTS controller called Static Synchronous Compensator STATCOM to improve the performance of power grid with Wind System is investigated. The essential feature of the STATCOM is that it has the ability to absorb or inject fastly reactive power with power grid. Therefore the voltage regulation of the power grid with STATCOM FACTS device is achieved. Moreover restoring the stability of the wind system at suddenly step up or down in wind speed is obtained with STATCOM. This paper describes a complete simulation of voltage regulation of a wind system using STATCOM. Conventional control technique as proportional plus integral controller , and intelligent techniques as FLC and ANFIS are used in this work. The control technique is performed using MATLAB package software. The dynamic response of uncontrolled system is also investigated under wide range of disturbances. The voltage regulation by using STATCOM whose output is varied so as to maintain or control output voltage in the system. The dynamic response of controlled system is shown and comparison between the uncontrolled system and the controlled system is described to assure the validity of the proposed controller. Also comparison between the proposed control methods scheme is presented. To validate the powerful of the STATCOM FACTS controllers, the studied power system is simulated and subjected to different severe disturbances. The results prove the effectiveness of the proposed STATCOM controller in terms of fast damping the power system oscillations and restoring the power system stability and voltage.